Profiling and Imaging Ion Mobility-Mass Spectrometry Analysis of Cholesterol and 7-Dehydrocholesterol in Cells Via Sputtered Silver MALDI - Xu, Libin (J Am Soc Mass Spectrom, 2015)
Profiling and imaging of cholesterol and its precursors by mass spectrometry (MS) are important in a number of cholesterol biosynthesis disorders, such as in Smith-Lemli-Opitz syndrome (SLOS), where 7-dehydrocholesterol (7-DHC) is accumulated in affected individuals. SLOS is caused by defects in the enzyme that reduces 7-DHC to cholesterol. However, analysis of sterols is challenging because these hydrophobic olefins are difficult to ionize for MS detection. We report here sputtered silver matrix-assisted laser desorption/ionization (MALDI)-ion mobility-MS (IM-MS) analysis of cholesterol and 7-DHC. In comparison with liquid-based AgNO(3) and colloidal Ag nanoparticle (AgNP), sputtered silver NP (10–25 nm) provided the lowest limits-of-detection based on the silver coordinated [cholesterol+Ag](+) and [7-DHC+Ag](+) signals while minimizing dehydrogenation products ([M+Ag-2H](+)). When analyzing human fibroblasts that were directly grown on poly-L-lysine-coated ITO glass plates with this technique, in situ, the 7-DHC/cholesterol ratios for both control and SLOS human fibroblasts are readily obtained. The m/z of 491 (specific for [7-DHC+(107)Ag](+)) and 495 (specific for [cholesterol+(109)Ag](+)) were subsequently imaged using MALDI-IM-MS. MS images were co-registered with optical images of the cells for metabolic ratio determination. From these comparisons, ratios of 7-DHC/cholesterol for SLOS human fibroblasts are distinctly higher than in control human fibroblasts. Thus, this strategy demonstrates the utility for diagnosing/assaying the severity of cholesterol biosynthesis disorders in vitro. [Image: see text]